ASSESSMENT OF DIETARY INTAKE IN 400 WOMEN WITH GESTATIONAL DIABETES - Majdoub, Marwa; ACH, Taieb; Slama, Nassim Ben Hadj; Abdelkrim, Asma Ben; Maaroufi, Amel; Chaieb, Molka (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVE Gestational diabetes (GD) is one of the most common complications in pregnancy, affecting nearly 14% of pregnancies Obesity in the mother-to-be, usually related to hypercaloric diet, is an important risk factor. Evaluation of the correlation between caloric intake and maternal-fetal complications. METHODOLOGY Retrospective study, concerning 400 pregnant patients with GD: fasting blood glucose or OGTT, between 2017 and 2019. Dietary intake was assessed by expert dieticians. RESULTS The mean age was 34.54 ± 5.51 years [19 -46]. A history of personal gestational diabetes was found in 16.8% of which 23% were complicated by macrosomia. Among the patients, 33.3% were obese before conception. Dietary survey: the average caloric intake was 2732.17 ± 605.87 calories with a diet considered hypercaloric: 60.9%. The average fat content was 34.35 ± 4.5% and protein 11.25 ± 3.35%. The average carbohydrate content was 54 ± 4.7% [39-69%] with a high-carbohydrate diet in 50.5% of patients. A high-calorie diet at the time of diagnosis was significantly correlated with the occurrence of obstetric complications (p=0.043) but not with fetal complications, including macrosomia (p=0.407). CONCLUSIONS Carbohydrates are an important source of energy for the mother and her fetus; it is recommended that all pregnant women have at least 175 g of carbohydrates per day. During gestational diabetes, it is essential to pay attention to the quantity (less than 35-45% of daily caloric intake) and type of carbohydrate: low glycemic index and slow digestion, to promote glycemic control and prevent maternal-fetal complications.